Enhancing the Surface Mechanical Properties of AL2618 Alloy Turbochargers Using a PLD Device with AI2O3 - Faraj, Sarah S.; Hadi, Nabil H. (Al-Khwarizmi Engineering Journal, 2024)
Pulsed laser deposition (PLD) has become a widely used technology for fabricating multicomponent thin films. In this research, nanomaterial Alfa-Al2O3 with a particle size of 30 ± 5 nm was deposited on the surface of AL-2618 alloy turbine blades. The microstructure, phase composition and the effects of a coating made from Alfa-Al2O3 nanomaterial were studied. PLD was employed to improve the mechanical performance of the aluminium alloy (AL-2618) used in turbocharger blades, primarily to reduce corrosion and erosion. To ensure high hardness and extended fatigue life, a 10 μm layer of aluminium dioxide was deposited on the surface of the aluminium alloy using PLD. The mechanical properties of the blade improved, as shown by hardness tests conducted on the samples. An energy-dispersive X-ray spectroscopy test was conducted before and after deposition. After depositing a nanolayer of Al2O3, the mechanical properties were enhanced. The hardness of the samples increased from 685 HLD to 781 HLD, and corrosion and erosion were reduced. The atomic percentage of oxygen deposited on the blade surface ranged from 0.6% to 0.8%, and the surface roughness (x) decreased from 49.5 µm to 22.8 µm because of the nanolayer applied via PLD.